ANALISIS PENGENAAN DAN PEMOTONGAN PAJAK PENGHASILAN (PPH) PASAL 23 PADA KANTOR BPJS KETENAGAKERJAAN CABANG RENGAT PADA MASA SEBELUM DAN SELAMA COVID 19 - Madina, Hanny Cahya; Junawan, Junawan; Hidayat, Rahmat (JURNAL PERPAJAKAN, 2024)
Cahya Madina, Hanny. 2021. “Analysis of the Imposition and Withholding of Income Tax (PPH) Article 23 at the Rengat Branch Office of BPJS Employment in the Period Before and During Covid 19”. D3 Taxation Study Program, Faculty of Social Sciences. Panca Budi Development University, Medan.Thesis. This study aims to determine how the mechanism of imposition and withholding of taxes in the period before and during covid 19. The research method used in this study is descriptive analysis. With this method, research data are compiled, interpreted, explained, and analyzed. The type of data used in this study uses qualitative data, the data is obtained from BPJS Employment Rengat Branch for the period March – December 2021. The results of this study conclude that: 1) BPJS Ketenagakerjaan Rengat Branch has made impositions and deductions that are in accordance with Minister of Finance Regulation Number 141 /PMK.03/2015 and also Law No. 36 of 2008. 2) There was a decrease in the amount of tax in 2020 with a difference in the Tax Baseline (DPP) of Rp. 39,962,981,-. and the difference in cutting rates of Rp 934,884, - due to a decrease in the budget due to limited activities during the Covid 19 Pandemic. 3). Some transactions are carried out by PKP that are not included in the NPWP by BPJS Employment so that the tariff cut is 4% of the Tax Imposition Basis (DPP).